Foundations for a human science of nursing: Gadamer, Laing, and the hermeneutics of caring. (24th November 2014) - Rolfe, Gary
Abstract The professions of nursing and nurse education are currently experiencing a crisis of confidence, particularly in the UK, where the Francis Report and other recent reviews have highlighted a number of cases of nurses who no longer appear willing or able to 'care'. The popular press, along with some elements of the nursing profession, has placed the blame for these failures firmly on the academy and particularly on the relatively recent move to all‐graduate status in England for pre‐registration student nurses. This has come to be known in the UK as the 'too‐posh‐to‐wash' argument, that there is an incommensurability between being educated to degree level and performing basic nursing tasks. I will argue in this paper that the diagnosis of the problem is substantively correct, but the formulation and the prescription are misguided and dangerous. I will suggest that the growing emphasis on research‐based and evidence‐based practice is the logical conclusion of an inappropriate scientific paradigm for nursing which is underpinned by the social sciences, by technical rationality, and by a focus on people. In contrast, I will suggest that a more fruitful way of thinking about and practising nursing and nurse education is to consider it as a human science with a focus on persons in which evidence for practice derives largely from practice itself. The history of the idea of a human science is traced from its roots in nineteenth century hermeneutics to the work of Gadamer and R.D. Laing in the 1960s, and I attempt to imagine a paradigm for nursing practice, scholarship, and education based on Laing's 'existential–phenomenological' approach with a focus on the endeavour to understand and relate to individual persons rather than to make broad prescriptions for practice based on statistical and other generalizations.